2022
DOI: 10.1038/s41387-022-00181-8
|View full text |Cite
|
Sign up to set email alerts
|

The independent association between vitamin B12 and insomnia in Chinese patients with type 2 diabetes mellitus: a cross-sectional study

Abstract: Background/objectives Insomnia is highly prevalent in patients with type 2 diabetes mellitus (T2DM). This study therefore evaluated the associations between various micronutrients and insomnia in patients with T2DM. Subjects/methods Between January 2018 and December 2020, a total of 418 T2DM patients with or without insomnia were recruited. Clinical and biochemical parameters, as well as micronutrient levels, were measured in each participant. Inso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
(60 reference statements)
2
2
2
Order By: Relevance
“…We also identified an association between gut microbial menaquinone synthesis (vitamin K2) I (MGB040) and a higher prevalence of sleep problems at baseline. There is a paucity of evidence documenting this relationship, but previous reports align with our findings [ 77 , 78 , 79 , 80 ] and warrant additional investigation due to their potential to support nutrigenomics interventions. Similarly, there was a significant association between microbial inositol degradation (MGB038) and a lower prevalence of sleep-related issues at baseline.…”
Section: Discussionsupporting
confidence: 86%
“…We also identified an association between gut microbial menaquinone synthesis (vitamin K2) I (MGB040) and a higher prevalence of sleep problems at baseline. There is a paucity of evidence documenting this relationship, but previous reports align with our findings [ 77 , 78 , 79 , 80 ] and warrant additional investigation due to their potential to support nutrigenomics interventions. Similarly, there was a significant association between microbial inositol degradation (MGB038) and a lower prevalence of sleep-related issues at baseline.…”
Section: Discussionsupporting
confidence: 86%
“…A study conducted in 2019 [22] found that vitamin B 12 levels did not significantly affect the severity of insomnia. Furthermore, it is of particular interest to mention than another study [24] found that vitamin B 12 levels were considerably higher in insomniac individuals, which does not correlate with our findings. Consequently, additional studies are needed to investigate the relation between cobalamin levels and insomnia.…”
Section: Plos Onecontrasting
confidence: 92%
“…We also identified an association between gut microbiome menaquinone synthesis (vitamin K2) I (MGB040) and a higher prevalence of sleep problems at baseline. Despite the paucity of evidence documenting this relationship, previous research provides context for our findings [8588] and warrants additional investigation. Similarly, we noted a significant association of microbial inositol degradation (MGB038) with a lower prevalence of sleep-related issues at baseline.…”
Section: Discussionmentioning
confidence: 67%